Defining personal utility in genomics: A Delphi study. Issue 3 (19th April 2017) - Kohler, J.N.; Turbitt, E.; Lewis, K.L.; Wilfond, B.S.; Jamal, L.; Peay, H.L.; Biesecker, L.G.; Biesecker, B.B.
Abstract : Background: Individual genome sequencing results are valued by patients in ways distinct from clinical utility. Such outcomes have been described as components of "personal utility, " a concept that broadly encompasses patient‐endorsed benefits, that is operationally defined as non‐clinical outcomes. No empirical delineation of these outcomes has been reported. Aim: To address this gap, we administered a Delphi survey to adult participants in a National Institute of Health (NIH) clinical exome study to extract the most highly endorsed outcomes constituting personal utility. Materials and Methods: Forty research participants responded to a Delphi survey to rate 35 items identified by a systematic literature review of personal utility. Results: Two rounds of ranking resulted in 24 items that represented 14 distinct elements of personal utility. Elements most highly endorsed by participants were: increased self‐knowledge, knowledge of "the condition, " altruism, and anticipated coping. Discussion: Our findings represent the first systematic effort to delineate elements of personal utility that may be used to anticipate participant expectation and inform genetic counseling prior to sequencing. The 24 items reported need to be studied further in additional clinical genome sequencing studies to assess generalizability in other populations. Further research will help to understand motivations and to predict the meaning and use of results. Abstract :